La Falta de Inscripción en el Registro Mercantil, Registro de la Propiedad y otros Registros, de las Promesas de Compra y Venta de Bienes Muebles e Bienes Inmuebles, Vulnera los Derechos Patrimoniales - Serrano Ortiz, César Israel (2023)
The present investigation is entitled: "THE LACK OF REGISTRATION IN THE COMMERCIAL REGISTRY, PROPERTY REGISTRY AND OTHER RECORDS, OF PROMISES TO PURCHASE AND SELL MOVABLE AND REAL ESTATE PROPERTY, VIOLATES PROPERTY RIGHTS", in which we carried out a Study of the purchase and sale promise and its problems at the time of registration. Many people hoping to have their own real estate trust real estate agents or builders and people who offer services for the sale of personal and real estate, with the promise of selling a property at easy-to-access plans, but in the end, years go by and they never deliver. the good offered. This problem is due to the fact that there is no regulation that protects the legal figure of the promise of purchase and sale, both in the Organic Law of the National System of Public Data Registries, as well as in the Property Registry Law and the Code of Commerce, thus opening the door for scams to exist without delivering what was promised. Let's not forget that the promise of sale is made in a Notary and therefore it is a public deed. Article 26 of the Notarial Law defines what is a Public Deed when regulating: Public deed is the parent document that contains the acts and contracts or legal transactions that people grant before a notary and that he authorizes and incorporates into his protocol. The acts and contracts or legal transactions ordered by the Law or agreed by the will of the interested parties will be granted by public deed. (Notarial Law, 2022) Article 19 of the Notarial Law, within the duties of Notaries, states the following: They are duties of Notaries: a) Receive, interpret and give legal form to the externalization of the will of those who require their ministry. 5 The reception of the externalization of will, may be done, physically or electronically, in accordance with the choice of the users. If a bill is presented, it must be signed by hand or electronically by one or more lawyers, including the professional registration number. The minutes may be subject to modifications made by the parties with the authorization of the notary, prior to the granting of the public deed... d) Incorporate daily into the protocol the public deeds that authorize and the documents that must be protocolized; (Ibid) Article 19 of the Organic Law of the National System of Public Data Registries, gives legal life to the Property Registrar, in which, it does not give it its functions, which entails a legal vacuum, which can lead to various interpretations. that it can lead to a legal error when carrying out its activities; in this Law it is essential that its functions be implemented, so that its activity does not violate the Law; The same occurs with Article 20, which regulates the Mercantile Registry. And within its functions it would be very appropriate to legalize and incorporate the registration of purchase and sale contracts. In Article 25 of the Property Registry Law, it is not determined that promises of sale are subject to registration in the Mercantile Registry. Similarly, Article 22 of the Commercial Code does not determine the duty to register a promise of sale. Despite this legal problem that the registration of a purchase and sale promise contract in the corresponding registry is not foreseen, the Law provides that said contract be elevated to a public deed before a Notary, for which reason, it gives an open letter so that many scammers see the opportunity to deceive many Ecuadorians to acquire a property in the future and they enrich themselves at the expense of others, inducing them to invest in acquiring a property in the future since they will be insured with a deed of promise of sale legalized before a Notary.